Gambaran Pasien Hambatan Komunikasi Verbal pada Tn I dengan Stroke Non Hemoragik di Desa Karangmangu Purwojati - Mega Yanti; Prasanti Adriani; Suci Khasanah (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The main cause of stroke is usually high blood pressure which causes blockage of blood circulation so that the supply of blood and oxygen to the brain decreases. Symptoms of a stroke are usually sudden numbness of the face, arm, hand, and leg on one side or part of the body, usually accompanied by a sudden, severe headache. Nursing problems that may arise in patients with non-hemorrhagic stroke are verbal communication barriers. The purpose of this research is to be able to provide nursing care for verbal communication barriers. At Mr. I with non-hemorrhagic stroke in Karangmangu Village, Purwojati. This research method uses a descriptive case study design. In this case study, the subject is Mr. I with verbal communication barriers in Karangmangu Village, Purwojati. The results show that the author makes a nursing care plan for Mr. I which includes communicaton. Evaluation after carrying out nursing actions in accordance with the nursing action plan, an evaluation is carried out to find out and monitor developments and assess how successful the nursing actions have been to Mr. I Evaluation carried out for 3 days. Verbal communication barriers related to neuromuscular disorders